2015
DOI: 10.1515/pjs-2015-0098
|View full text |Cite
|
Sign up to set email alerts
|

The Use Of Negative Pressure Wound Therapy (NPWT) In The Management Of Enteroatmospheric Fistula – Case Report And Literature Review

Abstract: c A S E R E P O R t SAn enteric fistula that occurs in an open abdomen is called an enteroatmospheric fistula (EAF) and is the most challenging complication for a surgical team to deal with. The treatment of EAF requires a multidisciplinary approach. First of all, sepsis has to be managed. Any fluid, electrolyte and metabolic disorders need to be corrected. Oral intake must be stopped and total parenteral nutrition introduced. The control and drainage of the effluent from the fistula is a separate issue. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In about half of the cases, different techniques for fistula isolation were used, whereas in the other half of patients, NPWT with/without special fistula patches/plugs were employed for fistula occlusion . Three possible outcomes are described for EAF treatment: spontaneous closure, conditioning of the surrounding wound, and conversion into an ECF with delayed surgical fistula elimination or definite ECF without need for fistula elimination . Furthermore, in 38.5% of the cases, there was spontaneous fistula closure during treatment, with higher probability in low‐output fistulas .…”
Section: Discussionmentioning
confidence: 99%
“…In about half of the cases, different techniques for fistula isolation were used, whereas in the other half of patients, NPWT with/without special fistula patches/plugs were employed for fistula occlusion . Three possible outcomes are described for EAF treatment: spontaneous closure, conditioning of the surrounding wound, and conversion into an ECF with delayed surgical fistula elimination or definite ECF without need for fistula elimination . Furthermore, in 38.5% of the cases, there was spontaneous fistula closure during treatment, with higher probability in low‐output fistulas .…”
Section: Discussionmentioning
confidence: 99%
“…Whether the use of VSD after abdominal surgery can lead to secondary intestinal injury and increase the incidence of intestinal fistulas is controversial. At present, an increasing number of studies have confirmed that the use of VSD does not increase the incidence of intestinal fistulas 21, 30, 34, 50, 55, 96, 127, 145, 148, 152, 154, 156…”
Section: Recommendationsmentioning
confidence: 95%
“…A total of 22 studies were included, one RCT, 110 one systematic review, 111 and 20 observational studies. 80 , 93 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 …”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations